Особенности развития техники обработки земли в Восточной Европе в раннем железном веке - Шрамко, Б. А. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary B. Shramko. Specific Development of Tilling Implements of Eastern Europe in the Early Iron Age In the article some problems of tilling implements is considered. It is worth noting that in 6-th century B. C. the iron coulter is emerge appear. From the 4-th century narrow iron share without of bush is diffunse in Eastern Europe. Different variety iron share this type (without burh) is apply approximately before 10 century A. B.